Առողջապահության տնտեսական արդյունավետության գնահատումը - Գոհարիկ Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Экономическая эффективность здравоохранения исследуется не с точки зрения отраслевой экономики, а с точки зрения рассмотрения проблемы по отдельным фазам воспроизводства, распределения и использования трудовых ресурсов. Соответственно этому в статье представляются методы расчета экономической эффективности здравоохранения. The article departs from the traditional methods of evaluating the efficiency of the entire healthcare system, instead proposing to evaluate separately the efficiency of different stages of services’ provision process; allocation and use of labor force. Based on the above-discussed approach, the article provides methodology for calculating the efficiency of the healthcare.
Keywords: Բժշկություն